2017
DOI: 10.1038/s41598-017-04420-2
|View full text |Cite
|
Sign up to set email alerts
|

Limited role of sessile acidophiles in pyrite oxidation below redox potential of 650 mV

Abstract: Pyrite oxidation by mixed mesophilic acidophiles was conducted under conditions of controlled and non-controlled redox potential to investigate the role of sessile microbes in pyrite oxidation. Microbes attached on pyrite surfaces by extracellular polymeric substances (EPS), and their high coverage rate was characterized by scanning electron microscopy (SEM), confocal laser scanning microscopy (CLSM) and atomic force microscopy (AFM). The dissolution of pyrite was negligible if the redox potential was controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…With the reduction of Fe 3+ to Fe 2+ and SO 4 2− to S 2− , the Eh decreased significantly, while the control and lime addition treatments were quite stable, suggested the lesser reducing reaction. It was reported that below the Eh of about 450 mV (vs. Ag/AgCl), pyrite oxidation was negligible even it was fully covered by bioleaching microbes on the surface [31]. So, in all the four treatments, the pyrite oxidation was very slow as their Eh were all lower than 450 mV; thus the pH in the column was not decreased, showing the effectiveness of the anaerobic condition to inhibition the pyrite oxidation.…”
Section: Physiochemical Properties In Different Treatmentsmentioning
confidence: 88%
“…With the reduction of Fe 3+ to Fe 2+ and SO 4 2− to S 2− , the Eh decreased significantly, while the control and lime addition treatments were quite stable, suggested the lesser reducing reaction. It was reported that below the Eh of about 450 mV (vs. Ag/AgCl), pyrite oxidation was negligible even it was fully covered by bioleaching microbes on the surface [31]. So, in all the four treatments, the pyrite oxidation was very slow as their Eh were all lower than 450 mV; thus the pH in the column was not decreased, showing the effectiveness of the anaerobic condition to inhibition the pyrite oxidation.…”
Section: Physiochemical Properties In Different Treatmentsmentioning
confidence: 88%
“…Our experimental conditions included high redox potential due to the high ratio of the predominant redox couple Fe 3+ /Fe 2+ as the result of sustained bacterial activity. Liu et al (2017) noted the importance of the difference between the redox and rest potentials for pyrite dissolution to soluble iron and sulfate. Our data showed how the different redox conditions established with the Eh and Es values at the same initial pH resulted in sulfate formation in the presence of bacteria or elemental sulfur formation in the abiotic control without bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Electrochemical study of the oxidation of a crystal pyrite electrode detected sulfate formation, together with S 8 , at the electrode potential at 0.7–0.8 V and pH 2 (Tu et al, 2017b). Liu et al (2017) studied the oxidation of pyrite electrode by sessile acidophiles. The bacteria had limited impact on pyrite dissolution at and below the redox potential of 650 mV (near the rest potential), but an increasing redox potential (e.g., spontaneously at the uncontrolled potential) resulted in pyrite dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors that affect pyrite dissolution, the solution Eh is the most critical and is directly correlated with rate. Below the redox potential of 650 mV (vs. SHE), pyrite is barely oxidized, even though microbes adhere on the pyrite surface [31,32]. It was reported that the pyrite oxidation was 5 times faster with the elevation of redox potential by 100 mV [33].…”
Section: Microbial Community and Activitymentioning
confidence: 99%